2015
DOI: 10.1007/978-3-319-25939-0_36
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Physical Activity Interventions for Older Adults: A Review

Abstract: Abstract. Most web-based physical activity interventions were built based on the principles of universal design but may have overlooked age-related impairments experienced by older adults. Thus, it is important to know how successful such web-based interventions are in enhancing older adults' physical activity levels despite these shortcomings. The objective of this study is to review published literature regarding interactive web-based interventions promoting physical activity among older adults. EBSCOhost, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Moreover, the effectiveness of delivering health-related information intended for behavior change through telehealth is equal to that of print-based delivery [ 10 ]. While telehealth presents a promising platform for conducting interventions, telehealth interventions need to be further examined in older populations [ 11 , 12 ], particularly in light of the COVID-19 pandemic [ 13 ]. Our pilot study sought to examine how a telehealth intervention changed activity profiles in older adults during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effectiveness of delivering health-related information intended for behavior change through telehealth is equal to that of print-based delivery [ 10 ]. While telehealth presents a promising platform for conducting interventions, telehealth interventions need to be further examined in older populations [ 11 , 12 ], particularly in light of the COVID-19 pandemic [ 13 ]. Our pilot study sought to examine how a telehealth intervention changed activity profiles in older adults during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…All the interventions (11/11, 100%) provided instructions on how to perform the behavior, which other authors have pointed out as the core of most web-based interventions [ 65 ]. Many (5/11, 45%) proposed automated feedback, which would be one of the most effective delivery modes leading to behavior change in adults [ 26 ]. Only 9% (1/11) of the interventions included a forum with peers, and it was underused by participants, which is inconsistent with other studies in which adults aged ≥50 years showed high use [ 66 ] and appreciation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…As motivation is an intrinsic factor (ie, each person must identify their own), increasing individual motivation among older adults may facilitate behavior change [ 76 ]. In this sense, future web-based interventions among older adults should target this determinant as a way to help them adopt healthy lifestyle habits [ 26 ]. This review also found that older adults appear to appreciate interventions that include support from a coach, which also supports their motivation for change and engagement with the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a health system named WeSihat [11]. In 2015, a group of researchers [9] reported a review regarding web based physical activity intervention for older adults. It discovered that only two study have shown negative outcomes and subsequently ten studies reveal positive result.…”
Section: Physical Activity Interventions For Older Adultsmentioning
confidence: 99%